Features of Microsoft Project integration in development of construction projects - Donenko, I.; Verba А.; Pastukhova, S. (Ways to Improve Construction Efficiency, 2019)
The article discusses the main mechanisms for managing industrial and civil construction projects. On the basis of this software package, the issues of improving control over the implementation of project tasks are solved.